Mengkritisi Disiplin Spiritual yang Salah Arah dalam Praktik Doa dan Puasa - Sitanggang, Murni Hermawaty (JURNAL LUXNOS, 2025)
The practice of fasting and prayer has long been a part of Christian worship rituals, believed to promote the spiritual growth of believers. However, even positive spiritual disciplines can become negative when misunderstood. This error dates back to biblical times, when God rebuked Israel's fasting and prayer (Isaiah 58). Jesus also repeatedly touched on the importance of fasting and prayer properly. Therefore, this article aims to examine the various errors in the practice of fasting and prayer that believers need to be aware of. The method used is a qualitative literature review approach. The conclusion reached is that fasting and prayer can be misguided if done without repentance. Fasting and prayer are also not a guarantee of salvation. Therefore, the practice of fasting and prayer truly requires a clear purpose, with a desire to draw closer to God, and as an expression of faith and dependence.